Vibrational Spectral Analysis and First Order Hyperpolarizability Calculations on (E)-N′-(furan-2-yl methylene) Nicotinohydrazide - Bharanidharan, S.; Saleem, H.; Subashchandrabose, S.; Suresh, M.; Nathiya, A.; Syed Ali Padusha, M. (Journal of New Developments in Chemistry, 2016)
Vibrational spectral analysis and first order hyperpolarizability calculations on (E)-N′-(furan-2- ylmethylene) nicotinohydrazide (F2CNH), a novel, organic, hydrozone Schiff base compound was synthesized and its structure was characterized by FT-IR, FT-Raman and UV-visible spectrum. The optimized molecular structure, vibrational frequencies and corresponding vibrational assignments of F2CNH were performed on the basis of TED analysis using SQM method. Natural boding orbital (NBO) assessment has been carried out to clarify the charge transfer or conjugative interaction and delocalization of electron density within the molecule. Electronic transitions were studied employing UV-visible spectrum and the observed values were compared with theoretical values. The first order hyperpolarizability and related properties of F2NH were calculated. Besides FMO’s MEP, mulliken atomic charge and various thermodynamic paramefress such as Zero-point energy, rotational constant and enthalpy were also calculated and analyzed.
Keywords: FT-IR; FT-Raman; TED; NBO; F2CNH